PTU-074 Vedolizumab in Primary and Autoimmune Sclerosing Cholangitis Associated Inflammatory Bowel Disease Pre and Post Liver Transplantation: A Case Series. (17th August 2016) - Lim, TY; Pavlidis, P; Pirani, T; Gulati, S; Samaan, M; Chung-Faye, G; Dubois, P; Irving, P; Hayee, B
Abstract : Introduction: Vedolizumab has been recently licensed by NICE for the management of moderate to severe inflammatory bowel disease (IBD). Currently, no data is available on the efficacy or safety of this treatment in the context of autoimmune liver disease (AILD) associated IBD, especially in those post-liver transplantation (LT). Methods: Case series from two UK, tertiary IBD centres. Patients with primary and autoimmune sclerosing cholangitis (PSC and AISC) associated IBD were identified from a prospectively kept database. Clinical activity was assessed using Harvey-Bradshaw Index (HBI) or Simple Clinical Colitis Activity Index (SCCAI) at baseline and end of follow up (response: drop in HBI/SCCAI >3, remission: HBI < 5, SCCAI <3). Quality of life (QoL) was assessed by the IBD-control-8 questionnaire. Continuous data are summarised as medians followed by range. Pre- and post-induction values were compared using the Wilcoxon test. Results: We identified 10 patients with ulcerative colitis (UC) and AILD. The median age was 33 years (19, 57), with a follow up of 6 months (3, 13). There were 6 patients with PSC and 4 with AISC [5 (50%) postLT)]. Clinical and/or endoscopically [Mayo score: 2 (2, 3)] active disease was the indication for vedolizumab initiation in all patients with 7 (70%) having failed antiTNFα therapy before. Concomitant medication included: Tacrolimus: 4 (40%), Prednisolone: 7 (70%), MMF: 2 (20%), Azathioprine: 2 (20%) and Mercaptopurine: 1 (10%). A clinical response was seen in 4/10 (40%) and one patient achieved clinical remission. Surgery was required for one patient during induction due to severe colitis. A drop in faecal calprotectin [667 (60, 1080) vs. 182 (20, 349), p = 0.06] and improvement in QoL were observed [5 (0, 13) vs. 13 (8, 16), p = 0.03]. There were no infectious or other identified adverse events associated to vedolizumab. Conclusion: Vedolizumab appears to be a safe treatment in IBD patients with AILD pre- and post-LT and appears to have reasonable efficacy even for difficult-to-treat luminal disease. Disclosure of Interest: None Declared